1999
DOI: 10.1111/j.1469-445x.1999.tb00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Separate receptors mediate oxytocin and vasopressin stimulation of cAMP in rat inner medullary collecting duct cells

Abstract: SUMMARYThe two neurohypophysial hormones arginine vasopressin (AVP) and oxytocin have actions in the inner medullary collecting duct (IMCD) where both peptides induce an increas8e in cAMP accumulation. The present study has employed a novel IMCD cell line to determine whether these two hormones induce cAMP accumulation via common or separate receptors, and to characterize the potential receptors responsible. Equal volumes of vehicle (150 mM NaCI) or hormone/antagonist solutions were added to aliquots of lo4 IM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
0
13
1
1
Order By: Relevance
“…Molecular phylogenetic analysis also showed that the putative lungfish V2-type receptor belongs to the V2-type receptor group of tetrapods and was distinguishable from the V1-type receptor or other neurohypophysial hormone receptor groups. It has been known that the V1-and V2-type receptors in tetrapods are coupled to the PLC/PKC pathway and AC/PKA pathway, respectively (Wargent et al, 1999;Kohno et al, 2003). In the present study, administration of AVT to CHO cells transfected with lungfish V1a-type receptor or V2-type receptor resulted in intracellular Ca 2+ mobilization and the accumulation of cAMP in a concentration-dependent manner, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular phylogenetic analysis also showed that the putative lungfish V2-type receptor belongs to the V2-type receptor group of tetrapods and was distinguishable from the V1-type receptor or other neurohypophysial hormone receptor groups. It has been known that the V1-and V2-type receptors in tetrapods are coupled to the PLC/PKC pathway and AC/PKA pathway, respectively (Wargent et al, 1999;Kohno et al, 2003). In the present study, administration of AVT to CHO cells transfected with lungfish V1a-type receptor or V2-type receptor resulted in intracellular Ca 2+ mobilization and the accumulation of cAMP in a concentration-dependent manner, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…OT binds to the V2 AVP receptor because of its structural similarity to AVP. Vasopressin and OT induce cAMP accumulation from a common ATP pool in inner medullary collecting duct cells, and the separate AVP V2 and OT receptor systems may be coupled to a common adenylate cyclase system (30). In addition to their peripheral effects, these peptides may also have other effects that could complement their physiological actions.…”
Section: Neurohypophyseal Hormones and The Control Of Sodium And Watementioning
confidence: 99%
“…3), the effect mediated by AVT V2-type receptors on both AQP1a and AQP1b function would involve stimulation of PKA and perhaps PKC. It is unsurprising that AQP1a is regulated by AVTRV2 given that PKA is the preferential signaling pathway associated with this receptor, and PKC signaling seems to play a minor role (Wargent et al, 1999;Warne, 2001). However, previous studies in frog demonstrated the V2-type receptor could also function via stimulation of PLC pathways, one of the alternative pathways for PKC (Acharjee et al, 2004;Zhu et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of AQP function can be achieved via different signaling pathways (Dibas et al, 1998). AVTR/AVPR V1a-type and ITR were shown to act via PKC, which uses phospholipase C (PLC), inositol-1,4,5-trisphosphate (IP3) or Ca 2+ intracellular signaling pathways (Wargent et al, 1999). In contrast, PKA, whose activity is dependent on cellular levels of cyclic AMP (cAMP), is preferentially used by AVT/AVP V2-type receptors (Wargent et al, 1999;Warne, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation